(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Consumption of energy drinks has an upward trend with acquiring a modern lifestyle between all age groups worldwide including Saudi Arabia. To assess the knowledge level, prevalence, pattern and determinants of consumption of energy drinks among Saudi population aged 15-25 years in Jeddah, KSA. Methods: A cross-sectional study was carried out including 384 Saudi male and female youth aged 15-25 years living in Jeddah using an online especially prepared, self-administered pilot-tested, pre-coded, and closed-ended questionnaire in Arabic. It included data about sociodemographic characters, knowledge about consumption patterns and perceived effects following consumption. Results: Mean age of consumers was 20.5 years ±2.69, p= 0.001, 9.9% married and 80.2% students. Total mean knowledge score was 54.6± 17.51. Significant knowledge about negative health effects were for heart, blood pressure, muscle size and fatigability level. 76.6% assumed that energy drinks were used to increase musculature. 94.3% did not recommend their use. Prevalence of consumption of EDs among the youth sample was calculated as 29.95%. Their pattern of use was significantly correlated with age (r= 0.708, p= 0.023) , gender (r= -0.861, p= 0.014), educational level (r= 0.614, p= 0.015), marital status (r= -0.721, p= 0.000), employment (r= -0.800, p= 0.001), activity level (r= -0.534, p= 0.032), dietary habits (r= 0.636, p= 0.026), BMI (r= -0.728, p= 0.004), and their knowledge score (r= 0.835, p= 0.000). Side effects that were more perceived: change in voice tone, increase musculature, abnormal hair distribution, increase in heart and respiratory rate, and anxiety level. Conclusion: Consumption of energy drink is a relatively popular practice among youth. They are consumed to increase alertness and musculature. The perceived negative effects include masculinization of females, increased anxiety level, sleep disturbances. Overall knowledge level is low. Consumption is correlated with age, gender, educational level, marital status, employment, activity, diet, BMI.